Investigation of destination image mediating effect on tourists' risk assessment, behavioural intentions and satisfaction - Yenal Yağmur; Akın Aksu (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: The purpose of the present study is to establish a model for the risk assessments of tourists and to determine whether destination image has a mediating effect in the relationship between perceived risk, behavioural intentions, and satisfaction. Methods: The study has a quantitative research design in which data were collected through questionnaires. To ensure the construct validity of the proposed model, first, confirmatory and exploratory factor analyses were performed, and then the structural equation modelling technique was used. Amos 22 and SPSS 22.0 programs were used for the analysis of the data. Results: As a result of research analysis, it has been found that cognitive image had a partial mediating role between the behavioural intentions and satisfaction the tourists (between perceived risk and satisfaction) whereas affective image had no mediating impact between the tourists' perceived risks, behavioural intentions, and satisfaction. Implications:This study has some theoretical and practical contributions. Considering that the halal tourism literature is a very new concept, it is thought that a model proposal for the field will contribute to the deepening and development of the literature on the one hand and will provide important concrete data to hotel managers and destination policy makers on the other hand.
Keywords: L83; C91; M3; 330; perceived risk; destination image; metacognition